Causal association between inflammatory bowel disease and hidradenitis suppurativa: A two-sample bidirectional Mendelian randomization study - Bao, Bingzhou; Zhu, Chao; Shi, Jian; Lu, Canxing (Frontiers in Immunology, 2023)
Background Epidemiological studies have revealed a link between inflammatory bowel disease (IBD) and hidradenitis suppurativa (HS). To determine whether IBD and HS are causally related, we used the Mendelian randomization (MR) approach. Methods A two-sample MR was performed using an analysis of 12,882 patients and 21,770 controls with IBD and its main subtypes, ulcerative colitis (UC) and Crohn’s disease (CD). A total of 409 cases and 211,139 controls without hidradenitis suppurativa (HS) were included in the data for this condition from various GWAS investigations. Odds ratios (ORs) with 95% confidence intervals (CIs) are used to estimate causal effects. Results The study assessed the causal relationship between HS and IBD in both directions. The risk of HS was increased by IBD (IVW OR = 1.34, 95% CI = 1.20-1.49, p = 2.15E-07) and, in addition, HS was affected by UC (IVW OR = 1.27, 95% CI = 1.13-1.43, p = 8.97E-04) and CD (IVW OR = 1.18, 95% CI = 1.08-1.29, p = 4.15E-04). However, there was no evidence of a causal relationship between HS and IBD or its subtypes (IBD IVW OR = 1.00, 95% CI = 0.96-1.05, p = 0.85; UC IVW OR = 0.99, 95% CI = 0.95-1.03, p = 0.65; CD IVW OR = 1.03, 95% CI = 0.98- 1.07, p = 0.28). Conclusion This study demonstrates that IBD and its subtypes have a causal effect on HS, whereas HS does not affect IBD. Gut-skin axis interactions may help to understand this association. Nevertheless, further studies are needed to clarify the pathophysiology of the causal relationship between IBD and HS.